ANALISIS PERHITUNGAN BIAYA PRODUKSI DALAM PENETAPAN HARGA POKOK PENJUALAN PADA USAHA PENGELOLAAN ES TEBU DI KECAMATAN TELANAIPURA KOTA JAMBI - Mellya Embun Baining; Mohammad Orinaldi; Wati, Azmida (Lembaga Pengembangan Kinerja Dosen, 2022)
koABSTRACTThe purpose of this study was to find out how to calculate the cost of sugar cane traders in Telanaipura District, Jambi City. The type of research used was qualitative research, while the data collection techniques used in this study were interviews and documentation. In determining the cost of production, two methods can be used, namely the full costing method and the variable costing method. Based on the results of the study, it can be concluded that the strategy used by traders, namely cost calculation and pricing is still using a simple method, not using the full costing method or the variable costing method. Have not calculated all costs incurred during the production process. The calculation of the cost of production is only based on the price of raw materials, labor costs and factory overhead costs, but the factory overhead costs have not been calculated entirely.Based on the results of the calculation of the full costing method, the variable costing and the calculation according to the trader shows different results from the costs of each production where the production costs with the full costing method produce a higher value than the variable costing method and the merchant calculation method. This is because the calculation of the cost of production using the full costing method includes all cost accounts, both variable and fixed.